Analisis Perlindungan Hukum Konsumen dalam Transaksi Digital di Indonesia - Dewi, Amelia Permata; Rahmadani, Fitri; Yanti, Aulia Rahma; Saputra, Boga (Universitas Batanghari Jambi, 2026)
This study examines legal protection for customers in digital transactions and the effectiveness of existing regulations, including the Consumer Protection Regulation, the Electronic Information and Transactions (ITE) Regulation, and the Personal Data Protection Regulation. Using a normative juridical approach, the study found that the legal framework is quite comprehensive, but its implementation is still hampered by weak oversight, low digital literacy, and limited dispute resolution mechanisms. The study concludes that there is a need to strengthen law enforcement, improve digital literacy, and optimize the role of business actors in transparency, data security, and after-sales service. Thus, the development of digital technology is changing consumer transaction patterns in Indonesia by providing convenience and efficiency, but also giving rise to risks such as fraud, unclear information, and misuse of personal data.